Synthesis of Bucephalandra Schott (Araceae: Schismatoglottideae) studies in Kalimantan, Indonesia: checklist, key, and updated distribution maps - Yuzammi; Erlinawati, Ina; Ni Putu Sri Asih; I Putu Gede P. Damayanto; Lulut D. Sulistyaningsih; Marlina Ardiyani; Himmah Rustiami; Joko Ridho Witono; Alex Sumadijaya; Ary Prihardhyanto Keim; Rayhanissa (Reinwardtia, 2025)
YUZAMMI, ERLINAWATI, I., ASIH, N. P. S., DAMAYANTO, I. P. G. P., SUMADIJAYA, A., SULISTYANING-SIH, L. D., ARDIYANI, M., RUSTIAMI, H., WITONO, J. R., KEIM, A. P. & RAYHANNISA. 2025. Synthesis of Bucephalandra Schott (Araceae: Schismatoglottideae) studies in Kalimantan, Indonesia: checklist, key, and updated distribution maps. Reinwardtia 24(2): 185‒198. — Bucephalandra, a member of the Araceae family, is an endemic rheophyte genus of Borneo. The majority (26 out of the 32 species) of this genus, are found in Indonesian Borneo (Kalimantan). Bucephalandra oblanceolata (M.Hotta) S.Y.Wong & P.C.Boyce, previously known from Brunei and Sarawak, has been identified in Kalimantan. This study presents a comprehensive overview of Bucephalandra in Kali-mantan, accompanied by a detailed map and an identification key.